Hearing Paul's voice insights for teaching and preaching - Boring, M. Eugene 1935- (Grand Rapids, Michigan William B. Eerdmans Publishing Company, 2020)
"Boring offers a historically informed and pastorally sensitive reading of the Pauline voices in the New Testament for contemporary preachers and teachers"--
Includes bibliographical references and index
Keywords: Bible -- Study and teaching; Bible -- Homiletical use